2011
DOI: 10.1080/00207144.2011.594749
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hypnotic Focused Analgesia on Dental Pain Threshold

Abstract: The rate, intensity, and selectivity of hypnotic focused analgesia (HFA) were tested with dental pulp stimulation. Thirty-one healthy subjects were hypnotized, and hypnotic suggestions were given for anesthesia of the right mandibular arch. A posthypnotic suggestion of persisting analgesia was also given. The pain threshold of the first premolar was bilaterally measured before, during, and after hypnosis using a pulp tester. During hypnosis, the pain threshold increased significantly (p < .0001) for both sides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 43 publications
5
42
0
Order By: Relevance
“…Times of permanence in icy Psychology water, higher during HFA than in usual consciousness condition, were also similar in HFA-P and HFA-R, and the reflex response to pain was comparable too, confirming that, as in our previous experience (Casiglia et al, 2007(Casiglia et al, , 2015(Casiglia et al, , 2016Facco et al, 2011), HFA is due to a real block of painful stimuli.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Times of permanence in icy Psychology water, higher during HFA than in usual consciousness condition, were also similar in HFA-P and HFA-R, and the reflex response to pain was comparable too, confirming that, as in our previous experience (Casiglia et al, 2007(Casiglia et al, , 2015(Casiglia et al, , 2016Facco et al, 2011), HFA is due to a real block of painful stimuli.…”
Section: Discussionsupporting
confidence: 75%
“…As usual in our Laboratory of Experimental Hypnosis at the University of Padua (Casiglia et al, 1997(Casiglia et al, , 2006(Casiglia et al, , 2007(Casiglia et al, , 2010(Casiglia et al, , 2012a(Casiglia et al, , 2012b(Casiglia et al, , 2015(Casiglia et al, , 2016Facco, Casiglia, Masiero, Tikhonoff, Giacomello & Zanette, 2011;Giordano, Tikhonoff, Tosello, Lapenta, & Casiglia, 2012;Tikhonoff et al, 2012;Tikhonoff, Senzolo, Lapenta, Palatini, & Casiglia, 2017), in designing the protocol, specific attention was paid to using standardized instruments commonly employed in physiology and cardiology in order to make the study repeatable. As previously demonstrated both by our Laboratory (Casiglia et al, 2007(Casiglia et al, , 2015(Casiglia et al, , 2016Facco et al, 2011) and by other research groups (Sharav & Tal, 2004;Chaves & Dworkin, 1997), hypnotic focused analgesia (HFA) prevents pain in a real, measurable and repeatable way, also reducing or even abolishing the reflex autonomic response to pain. We induced ischemic pain by immersing the participant's hand in icy water at 0˚C temperature (a procedure called cold pressor test, CPT, used by cardiologists in the study of the coronary reserve) (Mitchell, MacDonald, & Brodie, 2004;Peckerman et al, 1998;Sevre & Rostrup, 1999).…”
Section: Experimental Sessionmentioning
confidence: 99%
“…In preliminary setting, all participants individually underwent hypnotic induction through verbal suggestions with cues of relax and wellbeing, a method already used with success in previous experiments carried out by our research group (Casiglia et al, 1997a(Casiglia et al, , 2007(Casiglia et al, , 2010(Casiglia et al, , 2012bFacco et al, 2011;Priftis et al, 2011;Tikhonoff et al, 2012). Through the voice of an expert hypnotist, each participant was guided towards focusing his/her attention on a single idea, excluding any other external or internal stimuli.…”
Section: Methods Participantsmentioning
confidence: 99%
“…After spontaneous eyelid closure was obtained, participants were invited to concentrate on their own body from head to foot, whilst a feeling of heaviness and muscular relaxation was being suggested (Kaffman, 1981). According to previous papers published by the same research group (Casiglia et al, 1997a(Casiglia et al, , 2006(Casiglia et al, , 2007(Casiglia et al, , 2010(Casiglia et al, , 2012bFacco et al, 2011), verification of hypnosis was based on some signals, such as arm levitation, the easing of facial tension, a dropped lower jaw with a slight opening of the mouth, and slowing down of breathing rate. The analysis of these signals enabled the hypnotist to verify the participants were really hypnotized and to maintain or modify this condition by means of continuous appropriate suggestions.…”
Section: Methods Participantsmentioning
confidence: 99%
“…We consider hypnosis as a tool (Casiglia et al, 1994, and our research group previously demonstrated that hypnotic and post-hypnotic commands are able to act in physical world, increasing physical performance , dilating arterial and venous vessels (Casiglia et al, 2015a), producing local analgesia (Casiglia et al, 2007(Casiglia et al, , 2016Facco et al, 2011Facco et al, , 2013 and general anesthesia by blocking both non-trigeminal and trigeminal algic stimuli before they arrive to the brain sensitive areas, and reproduce the physical effects of hemorrhage (Casiglia et al, 1997), and more in general have effects that are measurable in a scientific laboratory with the methods of human physiology . We were therefore confident that the command «you are unable to corrugate» would be obeyed.…”
Section: Methodsmentioning
confidence: 99%